IMPLEMENTATION OF THE PROJECT «CLINICAL BASES OF INTERNSHIP» WHILE PREPARING STUDENTS WITH A SPECIALTY IN «PSYCHOLOGY AND PEDAGOGY OF PRIMARY EDUCATION» - Elena G. Gutsu; Nadezda N. Demeneva (Образование и наука)
The aim of this work is to test new approaches to the students’practice organization in pedagogical universities on the basis of the competence approach.Methods. Diagnosis of formedness competences is carried out on the basis of the analysis of products of activity during the students’ school internship.Results. Teachers’ experience of Nizhny Novgorod State Pedagogical University of K. Minin on implementation of the innovative project «Clinical Bases of Internship » is presented. The authors have created and approved the program of school internship for the students with specialty in «Psychology and Pedagogics of Primary Education» based on the concept of the integrated clinical practice developed in higher education institution. The program involves organizational, reflexive-analytical, active-practical and project blocks. Features of clinical approach to pedagogical education are considered; requirements to school as the base of clinical practice are listed. The main content of student teaching and its role in professional formation of future elementary school teachers is disclosed. Importance of students’ project group and individual activity (the subject has to correspond to interests of employers and real needs of school) are emphasized.Scientific novelty. Specifics of integrated clinical internship as a means of formation of professional metacompetences of undergraduate students are presented. The organization of pedagogical internship is reconsidered; theoretically it has to provide fast professionalizing of training, early immersion into a profession that will promote not only to successful formation of flexible pedagogical thinking, but also growth of professional motivation of students – development in them of the positive relation to work of the teacher, interest in communication with children of younger school age, and aspiration to pedagogical research creativity.Practical significance. The research implementations can be of interest and useful to teachers of pedagogical universities and colleges.